The Origin of the Literary Legend on Jūratė and Kastytis: Scientific Evaluations and the Question of Sources - Burba, Domininkas (Literatūra, 2022)
The article explains what may have led to the appearance of one of the most famous and popular legend in Lithuanian culture about the love of the Queen of the Baltic Sea, Jūratė, and the mortal fisherman Kastytis, and looks at the history of its research. According to most scholars, the legend “Queen of the Baltic Sea” was created by Liudvikas Adomas Jucevičius (Ludwik Adam Jucewicz, 1813–1846), a Lithuanian writer, ethnographer, folklorist, historian and translator. The article examines the first reviews of the story and explains how the academic world came to the conclusion that this source is not authentic. It also investigates which sources may have influenced Jucevičius’ story, including mythological plots and the literary works by other authors.
Keywords: literary legends; romanticism; positivism; mythology; folklore